Selection the best strategy for Comercialization Trygona Honey in The Time of Past Covid 19 Pandemic Using SAST and ECM A case study in Nort Lombok West Nusatenggara - Kholil, Kholil (Archives of Business Research, 2021)
Covid 19 has a very serious impact on small and medium businesses in Indonesia, There are only a few SMEs are able to survive. The trygona honey home industry is one of them. This business have been developed by most of the people of North Lombok West Nusa Tenggara. But they do not know to commercialize their products in order to increase their income and ensure sustainability of the business. The main objective of this study is to analyze and develop share value chain that encourages and increasing business actors’s income. Data collection through experts discussion and field study and then analyzed using Strategic Assumption Surfacing and Testing (SAST) and Exponential Comparison Matrix (ECM). The Results of Study showed that honey producers sell their products to companies through collectors at low prices, while the greater profits are enjoyed by collectors and companies. The most important aspects for share value chain is development of Value Chain interconnectivity system as a matching institution between honey producers and the market by involving BUMDES (Villages Owned Enterprise). While the most appropriate strategy to comercialize trygona honey is value added system at the producer.